Biochemical and immunological markers of over-training - Gleeson, M. (Journal of Sports Science & Medicine, 2002)
Athletes fail to perform to the best of their ability if they become infected, stale, sore or malnourished. Excessive training with insufficient recovery can lead to a debilitating syndrome in which performance and well being can be affected for months. Eliminating or minimizing these problems by providing advice and guidelines on training loads, recovery times, nutrition or pharmacological intervention and regular monitoring of athletes using an appropriate battery of markers can help prevent the development of an overtraining syndrome in athletes. The potential usefulness of objective physiological, biochemical and immunological markers of overtraining has received much attention in recent years. Practical markers would be ones that could be measured routinely in the laboratory and offered to athletes as part of their sports science and medical support. The identification of common factors among overtrained athletes in comparison with well-trained athletes not suffering from underperformance could permit appropriate intervention to prevent athletes from progressing to a more serious stage of the overtraining syndrome. To date, no single reliable objective marker of impending overtraining has been identified. Some lines of research do, however, show promise and are based on findings that overtrained athletes appear to exhibit an altered hormonal response to stress. For example, in response to a standardized bout (or repeated bouts) of high intensity exercise, overtrained athletes show a lower heart rate, blood lactate and plasma cortisol response. Several immune measures that can be obtained from a resting blood sample (e.g. the expression of specific cell surface proteins such as CD45RO+ on T-lymphocytes) also seem to offer some hope of identifying impending overtraining. If an athlete is suspected of suffering from overtraining syndrome, other measures will also required, if only to exclude other possible causes of underperformance including post-viral fatigue, glandular fever, clinical depression, poor diet, anaemia, asthma, allergies, thyroid disorders, myocarditis and other medical problems interfering with recovery.